Globalization and Marginalized Groups: Finding Durable Solutions for Internally Displaced Persons (IDPs) in the Democratic Republic of Congo - Estriani, Heavy Nala; Asyidiqi, Hasbi; Qomaria, Nurul (WIMAYA, 2025)
Globalization does not automatically align with equitable growth and development. Its progress has often been exclusionary, as reflected in the growing number of marginalized groups overlooked by global development dynamics. Among these groups, Internally Displaced Persons (IDPs) remain particularly neglected, receiving limited support and attention from the international community. This causes IDPs to experience more social vulnerability, exclusion, and deprivation in various sectors. The Democratic Republic of Congo (DRC) has one of the largest IDP populations worldwide. Conflict and violence, and frequent natural disasters, have become the main reasons for displacement. This paper aims to discuss the most feasible durable solution to be implemented in handling prolonged displacement in the DRC. Using qualitative methods, this paper used the concept of Internally Displaced Persons and also the concept of Durable Solutions in addressing these matters.